Composition floristique et diversité du peuplement ligneux en zone de savane soudanienne de la Côte d’Ivoire - Koffi Missa; Dramane Soro; Bernadin Dro; Mamidou Witabouna Koné (VertigO, 2022)
The woody flora of the Ivorian savannahs, despite botanical harvests carried out by some authors, is not much studied. Thus, the floristic potential of the woody region of Tchologo, with the city of Ferkessédougou as its capital, is not yet sufficiently known. This study aimed to characterize the flora of the Tchologo region in the north of the Ivory Coast. For this purpose, woody species have been identified and measured in areas of one hectare (200 m x 50 m) near three main areas of study. This inventory showed that the area is rich with 88 species, spread over 69 genera and 30 families. The average number of species ranges from 19.20 ± 4.7 on the Ferkessedougou-Tafiré axis to 22.66 ± 2.77 on the Ferkessédougou-Sinématiali axis. The dominant families are the Caesalpiniaceae (13%), the Combretaceae (8%) and the Euphorbiaceae (7%). A comparison of stem density indicated that the Korhogo-Ferkessédougou axis has the highest value. Analysis of floristic diversity has shown a higher diversity around the Ferkessedougou-Tafiré axis. These results attest that the flora of Sudan has a great ecological value